Glioblastoma-on-a-chip construction and therapeutic applications - Xie, Zuorun; Chen, Maosong; Lian, Jiangfang; Wang, Hongcai; Ma, Jingyun (Frontiers in Oncology, 2023)
Glioblastoma (GBM) is the most malignant type of primary intracranial tumor with a median overall survival of only 14 months, a very poor prognosis and a recurrence rate of 90%. It is difficult to reflect the complex structure and function of the GBM microenvironment in vivo using traditional in vitro models. GBM-on-a-chip platforms can integrate biological or chemical functional units of a tumor into a chip, mimicking in vivo functions of GBM cells. This technology has shown great potential for applications in personalized precision medicine and GBM immunotherapy. In recent years, there have been efforts to construct GBM-on-a-chip models based on microfluidics and bioprinting. A number of research teams have begun to use GBM-on-a-chip models for the investigation of GBM progression mechanisms, drug candidates, and therapeutic approaches. This review first briefly discusses the use of microfluidics and bioprinting technologies for GBM-on-a-chip construction. Second, we classify non-surgical treatments for GBM in pre-clinical research into three categories (chemotherapy, immunotherapy and other therapies) and focus on the use of GBM-on-a-chip in research for each category. Last, we demonstrate that organ-on-a-chip technology in therapeutic field is still in its initial stage and provide future perspectives for research directions in the field.